Study of outcome of pregnancy in patients with first-trimester bleeding per vaginum - Patel, Nayan G.; Patel, Megha S.; Shah, Sushma R.; Jani, Shaswat K.; Patel, Jayesh A.; Shah, Jalpa U. (International Journal of Advances in Medicine, 2017)
Background: To assess pregnancy outcome in women with threatened miscarriage in the first trimester. To study various maternal complication and outcome of labor in pregnancy affected by first-trimester bleeding. Methods: This prospective study was carried out by institute from May 2013 to April 2014. 100 patients were included with a history of amenorrhea and urine pregnancy test positive with bleeding per vaginum in the first trimester. Results: In this case series, 100 cases of first-trimester bleeding were studied. Majority of patients were multigravida (66%). In the present study, 40 patient (40%) had a history of previous abortion out of these 16 (40%) had non-viable outcome and 24 (60%) continue with the pregnancy beyond 20 weeks. Majority of patients (68%) presented with spotting, among those 59 (86.7%) had a favorable outcome and only 9 (13.3%) out of 68 patients were aborted. All 10 patients of heavy bleeding category aborted. 5 out of 22 patients of bleeding of moderate category aborted. First-trimester bleeding associated with pain has a poor outcome. Conclusion: First-trimester bleeding is not only associated with miscarriage but also with a higher rate of pregnancy complications. First-trimester bleeding is associated with an increased risk of certain pregnancy-related complications namely placental abruption, preterm labor, delivery of low birth weight infants and preterm premature rupture of membrane.